1975
DOI: 10.1203/00006450-197501000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Release of Insulin in Fetal, Nursing and Young Adult Rats: Studies in Vivo and in Vitro

Abstract: ExtractThe secretion of insulin in vivo and its synthesis and release by pancreatic islets in vitro were studied in rats at various stages of development. An oral glucose load caused a rapid and significant increase in the serum insulin level of pregnant rats and a slower response in their 21-day-old fetuses. Circulating free fatty acids (FFA) decreased in the dams, but did not change in the fetuses. A relative glucose intolerance was found in pups 1 hr, 5 days, and 10 days after birth. This was accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…The effective induction of liver P-pyruvate carboxykinase in the newborn rat is henceforth readily understandable, when the unique state of insulin regulation during neonatal period is considered. The sluggish reactivity of the pancreatic fl cells to glucose loading [6,7], the persistently low levels of serum insulin from birth to the third week of life [7], and the decreased sensitivity of tissues to insulin during this period allow for an expression of the effects of glucocorticoids. Thus, under these conditions, triamcinolone was able to increase P-pyruvate carboxykinase equally well in the liver and kidney of neonatal rats (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective induction of liver P-pyruvate carboxykinase in the newborn rat is henceforth readily understandable, when the unique state of insulin regulation during neonatal period is considered. The sluggish reactivity of the pancreatic fl cells to glucose loading [6,7], the persistently low levels of serum insulin from birth to the third week of life [7], and the decreased sensitivity of tissues to insulin during this period allow for an expression of the effects of glucocorticoids. Thus, under these conditions, triamcinolone was able to increase P-pyruvate carboxykinase equally well in the liver and kidney of neonatal rats (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During the perinatal period, plasma insulin sharply declines and remains at a low level over the first two postnatal weeks [7,8]. Injection of insulin in utero prior to birth prevents the subsequent emergence of P-pyruvate carboxykinase [3].…”
mentioning
confidence: 99%
“…In the adult, secretion of insulin in response to a constant glucose stimulus occurs in a biphasic mode with early and late peaks (8). Recently, Blazquez et al (3) and Philipps et al (23) have shown an absence or diminution in the early phase of insulin secretion in response to fetal glucose elevation. Yet the newborn lamb and other species of newborns exhibit relatively brisk biphasic insulin responses during glucose infusion shortly after birth (1, 18).…”
Section: Speculationmentioning
confidence: 99%
“…Serial infusions were performed only after a recovery period of at least 48 hr after the last infusion. Plasma arterial samples for glucose and insulin were obtained twice in the 30 min preceding infusion and then at I%, 3,5,10,20,30,60,90, and 120 rnin postinfusion. Maternal arterial glucose and insulin samples were obtained during the control period and at 30, 60, and 120 min postinfusion to assess possible changes in maternal homeostasis.…”
Section: Speculationmentioning
confidence: 99%
“…The onset of weaning (d 14 -17) in the suckling rat is a critical period during which immature enterocytes exhibit elevated responsiveness to insulin (1). At this time, plasma insulin levels rise markedly (2), whereas milk-borne insulin is still active (3), allowing optimal interaction of the hormone with intestinal IR, which are located on both endoluminal and basolateral membranes of the cell (4). After weaning, the 2-fold decrease in IR concentration is associated with a reduction in responsiveness of mature enterocytes to the hormone (1,5).…”
mentioning
confidence: 99%